Persekutuan Aktual di Tengah Pertemuan Virtual: Makna Persekutuan Ibadah dengan Platform Digital Audiovisual - Harianja, Mikael; Hasibuan, Ricky Pramono (JURNAL DIAKONIA, 2024)
The development of technology, especially in digital, has an impact on the church, one of which is the movement of Sunday worship fellowship using a digital platform in the form of audiovisual. This then raises the question of how to interpret the virtual meeting. In conducting the research, the author then uses descriptive qualitative methods and data collection techniques through literature review by comparing the understanding of fellowship in the understanding of fellowship in the Batak church, especially HKBP with literature that examines digitalization both theologically and praxis in Christian worship and then describes it. The result of the study that virtual meetings using audiovisual digital platforms can be actual if there is a concurrent attitude in conducting worship in this case in the dimension of time and mutual awareness of the presence of fellow worshipers.